MicroRNA-223 Suppresses IL-1β and TNF-α Production in Gouty Inflammation by Targeting the NLRP3 Inflammasome - Zhang, Quan-Bo; Zhu, Dan; Dai, Fei; Huang, Yu-Qin; Zheng, Jian-Xiong; Tang, Yi-Ping; Dong, Zeng-Rong; Liao, Xia; Qing, Yu-Feng (Frontiers in Pharmacology, 2021)
Introduction: MicroRNA-223 (MiR-223) serves as an important regulator of inflammatory and immune responses and is implicated in several auto-inflammatory disorders. Here, we measured miR-223 expression in acute and intercritical gout patients, after which we used RAW264.7 macrophages transfected with a miR-223 mimic/inhibitor to determine the function of miR-223 in monosodium urate (MSU)-induced gouty inflammation. Methods and Results: MiR-223 was detected among 122 acute gout patients (AG), 118 intercritical gout patients (IG), and 125 healthy subjects (HC). RAW264.7 macrophages were cultured and treated with MSU. Over-expression or under-expression of miR-223 was inducted in RAW264.7 macrophages to investigate the function of miR-223. Real-time quantitative PCR, ELISA and western blotting were used to determine the expression levels of miR-223, cytokines and the NLRP3 inflammasome (NLRP3, ASC and caspase-1). MiR-223 expression was significantly decreased in the AG group in comparison with the IG and HC groups (P<0.001,respectively). Up-regulated expression of miR-223 was observed after acute gout remission in comparison with that observed during gout flares in 30 paired cases (P<0.001). The abundance of the NLRP3 inflammasome and cytokines was significantly increased after RAW264.7 macrophages were treated with MSU (P<0.01, respectively), while that of miR-223 was significantly reduced (P<0.01). Up-regulation of miR-223 decreased the concentrations of IL-1β and TNF-α, as well as the NLRP3 inflammasome expression (P<0.01, respectively), while IL-37 and TGF-β1 levels were unchanged (P>0.05, respectively). Under-expression of miR-223 increased the concentrations of IL-1β and TNF-α, as well as NLRP3 inflammasome expression (P<0.01, respectively), while IL-37 and TGF-β1 levels were not influenced (P>0.05, respectively). Conclusion: These findings suggest that miR-223 provides negative feedback regulation of the development of gouty inflammation by suppressing production of IL-1β and TNF-α, but not by regulating IL-37 and TGF-β1. Moreover, miR-223 regulates cytokine production by targeting the NLRP3 inflammasome.